Pendidikan Al-Qur’an Sebagai Upaya Membentuk Karakter Anak Melalui Asmantoga di Boyolali Jawa Tengah - Cahyaningrum, Pinki; Cholis, M. Nashrokhuddin; Rofika, Ika Dina; Nilawaty, Azzah (Jurnal Riset dan Pengabdian Masyarakat, 2024)
Loss of character as a person who upholds the values of Pancasila. Such as negligence in carrying out worship to God Almighty, and loss of people's concern for the environment. In forming this character, various supporting factors are needed to be used as signposts in morals. In addition to these supporting factors, it is necessary to know about the conditions and conditions and potentials that exist in the environment. Since ancient times, Indonesia is famous as the best spice producing country in the world. In the empowerment of spices in several regions of Indonesia known as Asmantoga. Since ancient times, Indonesia is famous as the best spice producing country in the world. In the empowerment of spices in several regions of Indonesia known as Asmantoga. In this regard, to support declining moral and moral conditions by analyzing the conditions of the surrounding environment, community service activities in the KKN-T Kersodarma UIN Raden Mas Said Surakarta group 149 real work lecture program were carried out in Dusun. Soko, Village. Jenengan Palm Oil District, Boyolali Regency, In this case, members of the Real Work Lecture (KKN) group 149 have an innovation to preserve the living fence located in the cemetery area of Soko Hamlet, seeing the number of vacant land and plants that die because they are not maintained. This research program is a field research that uses qualitative methods. The sources of data obtained in this study are observations and interviews as well as from several journals and books. In its implementation, the Asmantoga empowerment program is carried out in accordance with the problems that have occurred by conducting a problem analysis together with the Soko Hamlet apparatus. The implementation of this activity involves TPQ students, this is intended for character building for the children of Soko Hamlet students to create a sense of care, responsibility and love for the environment. So that to create the formation of student character related to a sense of care, responsibility and love for the environment, an understanding is needed by providing education through a learning process that is manifested in a short learning design (RPP) about plants or environmental components and planting practices and awareness of the importance of preserving the environment. Keywords: Qur'an Education (TPQ), Character, Asmantoga